Eksistensi dan Relevansi Adat Nobat dalam Prosesi Pernikahan Masyarakat Bayan: Analisis Living Law Perspektif Antropologi Hukum - Aisyunnada Makky; Saifullah; Khoirul Anam (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines the preservation efforts of Adat Nobat as part of the cultural heritage of the Bayan community in North Lombok Regency through the lens of T.O. Ihromi’s legal anthropology theory. Adat Nobat is a traditional marriage ritual rich in social, spiritual, and moral values, playing a significant role in fostering family harmony and maintaining social stability. This tradition reflects the Bayan community’s understanding of law as a living cultural element (living law), in which customary norms function both as behavioral guidelines and mechanisms of social control. The findings reveal that each sequence of the Adat Nobat procession such as ulun dedosan, ajikrama, syahadat daya, and serong serah embodies legal and ethical teachings that reinforce the values of responsibility, loyalty, solidarity, and cooperation within family life. The preservation of this tradition is maintained through intergenerational cultural transmission, the active involvement of customary leaders, and the role of traditional institutions and the community in safeguarding the continuity of these cultural practices. Overall, the preservation of Adat Nobat, analyzed through T.O. Ihromi’s legal anthropology framework, demonstrates that customary law is an expression of culture that remains dynamic and continuously evolving. This customary law not only regulates social relations but also strengthens family resilience and maintains harmony between traditional values and the changing social dynamics within the Bayan community.